The cause and consequence of robot adoption in China: Minimum wages and firms’ responses - Richard B. Freeman; Xueyue Liu; Zhikuo Liu; Ran Song; Ruixiang Xiong (Fundamental Research)
We study the cause and consequence of firms’ robot adoption in China using novel panel data related to robots imported by firms in China from 2001 to 2012, when more than 80% of China’s robots were imported. We find that the rising minimum wages affect firms’ robot adoption and the effect is more significant for routine-intensive, labor-intensive and large firms. Moreover, employing robots significantly increases firms’ productivity, labor employment, average wages, and market share. These findings suggest that productivity gains from automation are partially passed on to workers in the form of more employment and higher labor income.